Editorial (Rupandehi Campus Journal, 2025)
Rupandehi Campus Journal is a multi-disciplinary academic journal dedicated to fostering critical thinking, scholarly inquiry, and informed dialogue. Established in 2015, it provides a vibrant platform for educators, researchers, and practitioners to share research and ideas across diverse fields, including English language and literature, education, mathematics, health sciences, social sciences, management, law, Buddhist studies, and environmental concerns. The journal also engages with pressing social and ethical issues, promoting a holistic approach to scholarship. Published by the Campus Research Cell, it upholds academic rigor and supports community-focused, solution-oriented research. Committed to open-access publishing, the journal ensures free and unrestricted access to its content, encouraging inclusive and equitable participation in academic discourse.